PENGARUH VARIASI WAKTU EKSTRAKSI α-SELULOSA DARI PELEPAH KELAPA SAWIT SEBAGAI BAHAN BAKU PEMBUATAN MIKROKRISTALIN α-SELULOSA - Aulia Muliana Harahap; Ika Ucha Pradifta (Jurnal Agro Fabrica, 2019)
The study about the supply of α-cellulose from palm frond as a raw material for microcrystalline α-cellulose by hydrolysis method using nitric acid (HNO3), sodium nitrite (NaNO2), sodium hydroxide (NaOH), sodium sulfite (Na2SO3), sodium hypoclorite (NaOCl), aquadest (H2O, and hydrogen peroxide (H2O2) was aiming to find out α-cellulose produced at the extraction time variation (minutes) approximately 90, 100, 110, 120, and 130, respectively. The parameter analysis of α-cellulose from palm oil frond as raw material for producing microcrystalline α-cellulose includes analysis of water content, α-cellulose yield, morphological analysis of α-celluloseyield, morphological analysis of α-cellulose by SEM (Scanning Electron Microscope), Fourier analysis Transform Infra-Red (FT-IR) α-cellulose, and analysis of linitas with XRD (X-Ray Powder Diffraction) α-cellulose. The results showed that the best extraction time was 100 minutes with the results of the parameter analysis as follows: yield of 40.59%, water content of 1.332% and already fulfilling the Indonesian Industry Standards. The results of the characterization using FT-IR showed that α-cellulose amorphous from was characterized by 2 maximum peaks of 20 = 22o, 20o. The crystalline index was